%I #8 Feb 02 2015 05:30:02
%S -2,-2,-3,2,-2,4,-4,2,1,5,-4,1,7,9,9,1,-3,9,8,7,7,9,11,5,-2,4,-3,-1,6,
%T 11,12,16,17,19,2,-5,-11,-10,-1,7,10,16,9,12,21,13,15,16,15,22,11,10,
%U 11,13,9,17,7,9,11,12,17,6,-4,3,7,7,15,27,21,25,28,35,37,43,43,41,31,31,20
%N a(n) = ((2*n)-th semiprime) minus 2*(n-th semiprime).
%F a(n) = A099981(n) - A075818(n).
%e a(1) = -2 because ((2*1)-th semiprime) - 2*(1st semiprime) = 6 - 2*4 = -2.
%Y Cf. A066066.
%K sign
%O 1,1
%A _Juri-Stepan Gerasimov_, Jun 02 2010
%E Entries checked by _R. J. Mathar_, Aug 12 2010